NSIDC Daily Precipitation Totals at Coastal and Island Russian Arctic Stations, 1940-1990 - NASA National Snow And Ice Data Center Distributed Active Archive Center; RU/FSR/HME/AARI (UCAR/NCAR - Research Data Archive, 2007)
"This data set contains precipitation data originally recorded in log books at 65 coastal and island meteorological stations, and later digitized at the Arctic and Antarctic Research Institute (AARI), St. Petersburg, Russia, under the direction of Vladimir Radionov. Records from most stations begin in 1940. Instrumentation was generally a rain gauge with Nipher shield until the early 1950s (for most stations), when the Tretyakov precipitation gauge replaced earlier instrumentation. Data have not been adjusted for gauge type or wind bias. Data from 1967 and later are corrected for wetting loss (this correction was made by observers as they recorded the station data).", quoted summary from NSIDC documentation.The data files and associated documentation were downloaded from NSIDC to this DSS dataset in January 2007. See the dataset documentation [http://rda.ucar.edu/datasets/ds488.0/#!docs] for more information.